Patients with psychiatric illness report worse patient‐reported outcomes and receive lower rates of autologous breast reconstruction. Issue 10 (11th June 2020) - Mehta, Sumarth K.; Sheth, Amar H.; Olawoyin, Olamide; Chouairi, Fouad; Gabrick, Kyle S.; Allam, Omar; Park, Kitae E.; Avraham, Tomer; Alperovich, Michael
Abstract: Psychiatric well‐being impacts on general satisfaction and quality of life. This study explored how the presence of psychiatric diagnoses affects patient‐reported outcomes in breast reconstruction and on selection of reconstructive modality. Patients who received breast reconstruction at a tertiary hospital between 2013 and 2018 and completed the BREAST‐Q survey were included. BREAST‐Q module scores were compared between patients who had a psychiatric diagnosis at presentation and the remaining cohort using t tests. General linear models (GLMs) were used to control for confounding factors. A chi‐squared test was used to assess the effect on reconstructive modality, and binary logistic regression was used to control for confounding factors. Of the 471 patients included, 93 (19.7%) had at least one psychiatric diagnosis. Cohorts did not differ significantly by age, BMI, race, ASA classification, or insurance status. Patients with a psychiatric diagnosis experienced a decrease in BREAST‐Q scores for the Psychosocial Wellbeing ( B  = 9.16, P  = .001) and Sexual Wellbeing ( B  = 9.29, P  = .025) modules. On binary logistic regression, patients with a psychiatric diagnosis were less likely to receive autologous reconstruction compared with implant reconstruction (OR = 0.489, P  = .010). The presence of psychiatric diagnoses is an independent predictor of decreased BREAST‐Q. Furthermore, there is a significant disparity in modality of reconstruction given to patients with psychiatric diagnoses. Further study is needed to evaluate interventions to improve satisfaction among at‐risk populations and evaluate the reason for low autologous reconstruction in this population.